Answer:
Inverse function: [tex]f^{-1}(x)=\frac{x}{3}[/tex]
Step-by-step explanation:
The inverse of a functon [tex]y=f(x)[/tex] is the function [tex]g[/tex] such that [tex]g(y)=x[/tex].
In this problem, the function that we have to reverse is
[tex]y=f(x)=3x[/tex]
In order to reverse the function, we do it in this way:
1) First, we isolate x and we write it as a function of y. Therefore:
[tex]x=\frac{y}{3}[/tex]
2) Then, we exchange the names of the variables, so:
[tex]y=\frac{x}{3}[/tex]
Therefore, the inverse function is
[tex]f^{-1}(x)=\frac{x}{3}[/tex]